Usefulness of genetic characterization of narcolepsy and hypersomnia on phenotype definition: a study in Portuguese patients - Martins-da-Silva, António (2014)
The determination of human leukocyte antigen (HLA) class II genotype is widely used to confirm the diagnosis of narcolepsy with or without cataplexy. The HLA genotyping is reliable, easy to perform and reassures the clinician. It is also less invasive than other methodologies and is in accordance with the autoimmune hypothesis for the origin of narcolepsy. AIM. To assess the usefulness of genetic markers (HLA) in the differential diagnosis between different sleep disorders and their relevance in the context of our population.